The Influence of Leadership on Students Organizational Performance - Ni Wayan Cahya Ayu Pratami (Universitas Warmadewa, 2022)
A person leadership style in leading is very influential and becomes a determining factor for increasing and decreasing employee performance, therefore it is clear that every company needs an effective leadership style because in this case it depends on the reliability and ability of members to operate work units. This research aims to examine the influence of leadership style on the performance of student organization members. This type of research is a type of quantitative research using survey research methods and data collection in this study using a questionnaire in the form of written statements given to respondents. The data obtained in this study is based on the answers of the respondents to the questionnaire distributed to 30 respondents who were taken by random sampling. The data analysis in this study used simple regression analysis, and testing the coefficient of determination, with the t test. From the results of the analysis of research data, it was found that there was an influence of the leadership style applied by the leadership of students’ organisation on members performance, this can be seen with a significance of =0.05 with a t-test result of 5.055 and a significance <0.05 (0.000<0.05), meaning that the hypothesis can be concluded that Ho is rejected and Ha received. So, it can be concluded that leadership style has a direct positive effect on members performances at Students Organisaion